Depression status and functional outcome of patients with ischemic stroke and the impact on caregivers living in Chengdu: a cross-sectional study - He, Lanying; Wang, Jian; Wang, Feng; Wang, Lu; Liu, Yinglin; Zhou, Fanfan; Xu, Fan (Frontiers in Psychiatry, 2023)
Objectives To investigate the associations between risk factors and depression symptoms in ischemic stroke (IS) survivors and the effect of IS survivors’ depression status and functional outcomes on caregiver burden in Chengdu, China. Methods In this cross-sectional study, we recruited a convenience sample of patients with IS and paired caregivers living in Chengdu from February 2022 to May 2022. Depression symptoms were assessed using the 17-item Chinese Hamilton Depression Rating Scale, the social support of patients was assessed using the perceived social support scale (PSSS), caregiver burden was assessed using the Zarit burden interview (ZBI). Multivariable logistic regression analysis was used to analyze the data between risk factors and depression symptoms, and multiple linear regression models were constructed to examine the depression symptoms and functional outcomes of stroke survivors, and caregiver burden. Results In total, 966 IS survivors and paired caregivers were included in this study. Among IS survivors, 35.51% (343/966) experienced depression. Age [adjusted odds ratio (aOR), 1.02; 95% confidence interval (CI), 1.00–1.04; p = 0.036], the National Institutes of Health Stroke Scale (NIHSS) score (aOR, 1.57; 95% CI, 1.47–1.68; p < 0.001), and PSSS score (aOR, 0.86; 95% CI, 0.84–0.89; p < 0.001) were associated with an increased risk of depression. The NIHSS score (b = 2.57, p < 0.001), patients’ depression status (b = 2.54, p < 0.001), duration of care (b = 0.359, p = 0.006), and social support of caregivers (b = −0.894, p = 0.038) were significantly associated with the ZBI score. Conclusion The PSSS score was a major risk factor for the development of depression in IS survivors, and patients’ depression status and severe functional deficits had a negative impact on the ZBI score of the main caregivers. Social support can reduce the ZBI score.